(385) Lectures On Graph Theory محاضرات عن نظرية الرسم البياني - Saaty, T. L. (The Institute Of National Planning., 2018)
in recent years, burgeoning technology has imposed its heavy demands on mathematics to provide tools and methods to formulate and solve a large and varies number of problems. even in pure mathematics one finds an adaptation of ideas that is suitable for a class of practical problems.